Renewable energy driven lighting system and its power saving - Daniel, Dincy (Nanyang Technological University, 2021)
There has been an increasing trend in the consumption of energy resources around the world. This increase consumption leads to global warming due to the burning of non-renewable resources like petroleum, LNG, etc.